THE ROLE OF CITIZENSHIP BEHAVIOR OF ALUMNI TOWARDS THEIR ALMAMATER: A DRIVER OF FINANCIAL AND SOCIAL GIVING BEHAVIOUR - Fitri Wulandari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
Specifically, the purpose of this study is to analyze the essence of both the direct or indirect role of alumni’s satisfaction with their alma mater. The higher alumni’s satisfaction will further encourage alumni’s involvement,and alumni’s engagementindicatesthat it will influence citizenship behavior,and its influence in increasing financial and social giving behavior. The samplesof this study arewere alumni of the Faculty of Economics and Business in Surakarta, with samplesof 161 alumni. Sample technique used in this study is anon-probability samplingbecause of the representation of large samples that need attention and the sample used is different for each level. Based on the research model built, the data are analysed by using the Structure Equation Model (SEM) and the opened questions are strengthen withinterviews with alumni. The results of the study explain that alumni’s satisfaction influence alumni’s involvement and alumni’s engagement. The results of the study also show that there is aninfluence of alumni’s involvement and alumni’s engagement towards citizenship behavior, and a influence citizenship behavior towards financial and social behavior.The result of this study supports the theory of discretionary collaborative behavior, where the effect of alumni satisfaction on alumni involvement is proven. This is indicated by path coefficients showing the strongest results. The results also showthat the effect of citizenship behavior on social giving behavior is greater than that of citizenship behavior on financial giving behavior.